The Education of Henry Adams. - Adams, Henry (Oxford world's classics., 1999)
As a journalist, historian and novelist born into a family that included two past presidents of the United States, Henry Adams was constantly focused on the American experiment. The Education of Henry Adams (1918) recounts his own and the country's education from 1838, the year of his birth, to 1905, exploring America as both a success and a failure and voicing his deep scepticism about mankind's power to control the direction of history. Written with immense wit andirony, reassembling the past while glimpsing the future, Adams's vision expresses what Henry James declared the |complex fate' to.